The Dynamics of Population Growth, Differential Fertility, and Inequality - Lam, David (American Economic Review, 1986)
This paper analyzes the effects of income differentials in fertility on Lorenz curves and standard inequality measures. The role of intergenerational mobility is examined and incorporated into counterfactual simulations based on Brazilian data. Two standard inequality measures move in opposite directions in both the steady state and the transition in response to the elimination of fertility differentials. The counterfactuals confirm the theoretical predictions of misleading intertemporal inequality comparisons in the presence of differential fertility.